Rational design and improvement of the dimerization‐disrupting peptide selectivity between ROCK‐I and ROCK‐II kinase isoforms in cerebrovascular diseases. Issue 6 (29th January 2020) - Gu, Zhengtian; Yan, Tingting; Yan, Fuling
Abstract: Human rho‐associated coiled‐coil forming kinases (ROCKs) ROCK‐I and ROCK‐II have been documented as attractive therapeutic targets for cerebrovascular diseases. Although ROCK‐I and ROCK‐II share a high degree of structural conservation and are both present in classic rho/ROCK signaling pathway, their downstream substrates and pathological functions may be quite different. Selective targeting of the two kinase isoforms with traditional small‐molecule inhibitors is a great challenge due to their surprisingly high homology in kinase domain (~90%) and the full identity in kinase active site (100%). Here, instead of developing small‐molecule drugs to selectively target the adenosine triphosphate (ATP) site of two isoforms, we attempt to design peptide agents to selectively disrupt the homo‐dimerization event of ROCK kinases through their dimerization domains which have a relatively low conservation (~60%). Three helical peptides H1, H2, and H3 are split from the kinase dimerization domain, from which the isolated H2 peptide is found to have the best capability to rebind at the dimerization interface. A simulated annealing (SA) iteration method is used to improve the H2 peptide selectivity between ROCK‐I and ROCK‐II. The method accepts moderate degradation in peptide affinity in order to maximize the affinity difference between peptide binding to the two isoforms. Consequently, hundreds of parallel SA runs yielded six promising peptide candidates with ROCK‐I over ROCK‐II (I over II [IoII]) calculated selectivity and four promising peptide candidates with ROCK‐II over ROCK‐I (II over I [IIoI]) calculated selectivity. Subsequent anisotropy assays confirm that the selectivity values range between 13.2‐fold and 83.9‐fold for IoII peptides, and between 5.8‐fold and 21.2‐fold for IIoI peptides, which are considerably increased relative to wild‐type H2 peptide (2.6‐fold for IoII and 2.0‐fold for IIoI). The molecular origin of the designed peptide selectivity is also analyzed at structural level; it is revealed that the peptide residues can be classified into conserved, non‐conserved, and others, in which the non‐conserved residues play a crucial role in defining peptide selectivity, while conserved residues confer stability to kinase‐peptide binding. Abstract : Peptide selectivity between ROCK‐I and ROCK‐II is optimized by using a simulated annealing iteration method. The method accepts moderate degradation in peptide affinity in order to maximize the affinity difference between peptide binding to the two isoforms. Binding analysis confirms that the designed peptide selectivity is increased considerably relative to wild‐type peptide. The non‐conserved residues play a crucial role in peptide selectivity, while conserved residues confer stability to kinase‐peptide binding.